Management with Values and Its Impact on Organizations’ Success - Alboqami, Nadha Mutlaq (Journal of Economic, Administrative and Legal Sciences, 2020)
The main objective of the research is to determine management with values ​​and their impact on the success of organizations by answering the following questions:1- What is value management and when did it arise? What is its importance and steps?2- What are the elements of applying values ​​management and what are its obstacles?3- What is the relationship between the application of value management and the success of organizations? The researcher used the documentary descriptive methodology by reviewing the books and literature that discussed the values ​​and the success of the organizations. It reached a set of results, the most important of which are:1- The administration of values ​​has a new style of management that has made profound changes in the management environment and in various organizations by providing better services to beneficiaries and better performance for workers.2- The management by values provides ​​many techniques that play an important role in the success of organizations, namely:A- It helps to understand the style and philosophy of managementB- It helps to think about partnership in actionC- Leads to avoid frustrating factors. The research concluded by providing a number of recommendations, including:1- Encouraging governmental and private organizations to adopt the theory of ​​management by values because of its importance for individuals and organizations.2- The necessity of paying more attention by the higher departments in the organizations on how to achieve value compatibility (personal values, organizational values) to increase the loyalty of workers towards their organization.
Keywords: management; management by values; organizations success